Assessing the Sustainability of Agroforestry Systems in South Lampung Regency, Indonesia: A Case Study from Register 6 Way Buatan - Fikri Syahputra; Ainul Mardliyah; Bigi Undadraja (Universitas Muhammadiyah Malang, 2025)
This study provides a multidimensional sustainability assessment of the agroforestry system in Register 6 Way Buatan, South Lampung Regency. We employed a mixed-methods approach, combining descriptive and inferential analysis. The research site, Karya Tunggal Village, was selected purposively due to its designation as a registered agroforestry area. From a population of 550 agroforestry farmers, we selected a sample of 55 respondents. We evaluated sustainability using the Rapid Appraisal for Agroforestry System (RAP-AFS) method, which integrates Multi-Dimensional Scaling (MDS) for ordination analysis, Leverage analysis to identify key factors, and Monte Carlo analysis to assess uncertainty. The results demonstrate that the agroforestry system achieves a highly sustainable status on the ecological and economic dimensions and a moderately sustainable status on the social dimension. Leverage analysis identified the most critical attributes influencing sustainability: land conservation practices, soil cultivation techniques, profitability of agroforestry, income from non-agroforestry enterprises, local employment rates, and the community's dependency on agroforestry resources. These findings offer critical insights for policymakers and land managers aiming to enhance the long-term viability of integrated agroforestry systems.